Catalpol protects rat ovarian granulosa cells against oxidative stress and apoptosis through modulating the PI3K/Akt/mTOR signaling pathway. Issue 4 (17th April 2020) - Yan, Jin; Deng, Disi; Wu, Yeke; Wu, Keming; Qu, Jie; Li, Fei
Abstract: Disrupted follicular development may result in increased follicular atresia, which is a crucial mechanism of various ovarian pathologies. It has been demonstrated that oxidative stress is associated with disrupted follicular development. Catalpol is a natural compound that has been found to possess antioxidative stress. However, the effects of catalpol on oxidative stress-induced disrupted follicular development remain unclear. In the present study, we evaluated the protective effect of catalpol on hydrogen peroxide (H2 O2 )-induced oxidative damage in granulosa cells (GCs), which play crucial roles in the follicular development. Our results showed that catalpol significantly improved cell viability, reduced reactive oxygen species (ROS) and malondialdehyde (MDA) production, and elevated superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activities in H2 O2 -induced GCs. Catalpol treatment caused significant increase in bcl-2 expression, and decreases in bax and caspase-9 expressions. Compared with the H2 O2 -induced GCs, caspase-3 activity in catalpol-treated cells was markedly decreased. Furthermore, catalpol caused significant activation of PI3K/Akt/mTOR pathway in GCs in response to H2 O2 stimulation. Additionally, inhibition of this pathway reversed the inhibitory effects of catalpol on H2 O2 -induced oxidative injury and apoptosis in GCs. In conclusion, these findings suggested that catalpol protected GCs from H2 O2 -induced oxidative injury and apoptosis via activating PI3K/Akt/mTOR signaling pathway. Thus, catalpol might serve as a therapeutic approach for regulating disrupted follicular development.